Pertanggungjawaban Korporasi Dalam Tindak Pidana Korupsi: Studi Kasus Putusan Pengadilan Tinggi Tipikor Banjarmasin No.04/Pid.Sus/2011/Pt.Bjm - Russel Butarbutar (Universitas Jayabaya, 2016)
Accountability of the corporation in the form of corruption in the procurement of goods and services in the field of construction can be realized by using the theory of corporate punishment such as: the theory of vicarious liability, the identification theory, strict liability theory,corporate organ theory , the theory of corporate culture, doctrine of dele- gation theory, the theory of corporate law reactive, the doctrine of aggregation theory. Law enforce- ment officials are free to choose the theory and doctrine based on the case at hand, which is important to always pay attention to the principles of ensnaring geenstrafzonderSchuld (actus non facitreum nisi menssir rea) by referring to legislation corporate already exists. Offenses of corruption and crime that often occurs in the procurement of goods/services that are common construction in accordance with Act No.31 of 1999 such as: a crime against the state financial harm to the law or abuse of power, bribery offense group, group evasion offense in the post, extortion offense in office, deeds offense, offense relating to an interest in the procurement, and gratification